Correction: Quantification of Collagen Ultrastructure after Penetrating Keratoplasty - Implications for Corneal Biomechanics. - Craig Boote; Erin P Dooley; Steven J Gardner; Christina S Kamma-Lorger; Sally Hayes; Kim Nielsen; Jesper Hjortdal; Thomas Sorensen; Nicholas J Terrill; Keith M Meek (PLoS ONE)
[This corrects the article on p. e68166 in vol. 8.].